Nicaragua’s agroecological transition: Transformation or reconfiguration of the agri-food regime? - Schiller, Katharina J.F.; Godek, Wendy; Klerkx, Laurens; Poortvliet, P. Marijn (Informa UK Limited, 2019)
Agroecology started to amplify agroecology in Nicaragua in the 1980s and was translated into national policy in 2011. Using the Multi-Level Perspective on sustainability transitions (MLP), this paper explores whether the rise of agroecology has fundamentally transformed Nicaragua’s agri-food system. Drawing on the findings of a qualitative study including a range of agroecological actors and organizations, we create a rich innovation history timeline of Nicaragua’s agroecology development at different levels – the agroecological niche (space in which heterogenous actors nurture innovations) and the regime (dominant agri-food system paradigm). MLP analysis is used to explore the extent to which agroecology’s growth has transformed the national agri-food regime. We find that although the term ‘agroecology’ is used widely by government, incentives for transitions to agroecology are only weakly implemented. This stems partly from the co-optation of the agroecological niche’s discourse by regime actors. Currently, it seems the transition process is not a reconfiguration of the agri-food system, but rather that agroecology has been added to the regime without deeper changes.